DIPLOMATIC CHALLENGES AND GLOBAL SECURITY: APPROACHES TO CONFLICT RESOLUTION - Ergasheva Feruzabonu Odiljonovna (TADQIQOTLAR.UZ, 2025)
In an increasingly interconnected world, diplomatic challenges and global security issues are more complex than ever. From regional conflicts to international terrorism, the threats facing nations today require innovative and collaborative approaches to conflict resolution. This article explores the multifaceted nature of these challenges and examines various strategies that can be employed to promote peace and stability in the global arena.